Columnar Metaplasia in the Esophageal Remnant After Esophagectomy: A Common Occurrence and a Valuable Insight Into the Development of Barrett Esophagus. Issue 6 (December 2016) - Dunn, Lorna J.; Burt, Alastair D.; Hayes, Nicholas; Griffin, S. Michael
Abstract : Objective: This study aimed to establish the incidence of postesophagectomy columnar metaplasia and dysplasia, and the timescale over which it develops. It also aimed to assess if this epithelium is molecularly similar to sporadic Barrett esophagus, thereby confirming suitability as a research model. Background: Metaplasia in the esophageal remnant after esophagectomy is well described, but incidence and the potential for dysplasia are uncertain, and the clinical relevance unclear. Although proposed as a model for Barrett esophagus, no large studies have examined the molecular phenotype of postesophagectomy metaplasia. Methods: Patients underwent prospective endoscopic evaluation having previously undergone esophagectomy. The macroscopic appearance of the esophageal remnant was noted and biopsies taken. Specimens were stained using hematoxylin and eosin and by immunohistochemistry for cytokeratins 7 and 20, and Chromogranin A—proteins which have a well described expression pattern in sporadic Barrett esophagus. Results: Of the 126 eligible patients, 45 (36%) had evidence of metaplasia. There were no cases of dysplasia. Nonintestinalized columnar epithelium occurred earlier than specialized intestinal metaplasia (median 4.8 vs 8.1 yr; P = 0.025). Thirty-seven samples underwent immunohistochemical analysis. A classic cytokeratin 7/20 staining pattern was present in 23 cases (62%), within the prevalence range reported for sporadic Barrett. Conclusions: Columnar metaplasia is common following esophagectomy, but the absence of dysplasia in this large cohort is reassuring. Presence of specialized intestinal metaplasia is associated with increased time from surgery, suggesting this represents later disease. Immunohistochemistry staining is similar to sporadic Barrett, suggesting that this group of patients represent an accurate human model for the development of Barrett.